Secondary antiphospholipid syndrome in systemic lupus erythematosus – screening, diagnosis and treatment methods - Andrei-Bogdan Mihailescu; Ioana Cristina Saulescu; Daniela Opris-Belinski; Andra Balanescu; Violeta Bojinca; Florian Berghea; Laura Groseanu; Cosmin Constantinescu; Andreea Borangiu; Sanziana Daia-Iliescu; Diana Mazilu; Magda Negru; et al. (Romanian Journal of Rheumatology, 2022)
Systemic Lupus Erythematosus is the hallmark of autoimmune diseases, being characterized by multiple organ involvements and immune abnormalities, amongst which the presence of antiphospholipid antibodies with or without specific clinical manifestations (vascular thromboses and pregnancy morbidities) has a significant impact on the disease course, both short and long term, causing the accumulation of irreversible damage. This study evaluates the aforementioned impact, highlighting the importance of very early screening for these antibodies.